PENINGKATAN INFRASTRUKTUR DRAINASE PURA PEJENENGAN DADIA TEBEN DAYANG, DESA SIBETAN, KECAMATAN BEBANDEM, KAB. KARANGASEM - I Gusti Agung Gede Nodya Dharmastika; Putu Gede Suranata; Putri Ayu Devy Permata Sari (Universitas Warmadewa, 2025)
This community service activity was carried out as an academic contribution to support the enhancement of development planning capacity at the village level. The program aimed to assist Desa Adat Sibetan, located in Bebandem District, Karangasem Regency, in preparing a Cost Budget Plan and a funding proposal for the construction of a Retaining Wall in the traditional cemetery area, which has a high risk of landslides. The main problems faced by the community partners were the limited technical capacity of village officials in preparing systematic planning documents and the lack of understanding of funding proposal mechanisms in accordance with government standards. The implementation method consisted of several structured stages, including initial coordination and need assessment with village officials, field observations and surveys, preparation of work item lists and volume calculations, material unit price surveys in the Karangasem region, and unit price analysis based on construction technical standards. These stages were followed by technical assistance and Focus Group Discussions (FGDs) to help village officials understand the principles of budget planning and the procedures for preparing funding proposals independently. A participatory approach was applied throughout the process to ensure effective knowledge transfer, capacity building, and active community involvement in decision-making. The results showed that the total cost estimation for the construction of the Retaining Wall at the Setra of Desa Adat Sibetan reached IDR 3,567,984,223.00. The cost estimation was prepared based on actual field survey data and the latest material price adjustments in Karangasem Regency, resulting in an accurate and accountable cost estimate that can serve as a valid basis for submitting funding proposals to local government agencies and development support institutions. Overall, this program successfully produced practical outputs in the form of an applicable RAB document and a complete proposal, while also enhancing the technical and administrative planning capacity of the Sibetan village officials in managing infrastructure development. Furthermore, this activity contributed to strengthening participatory-based governance, promoting transparency and accountability in village financial management, and aligning with the Sustainable Development Goals (SDGs), particularly in the areas of resilient infrastructure, sustainable development, and community empowerment partnerships.